The Influence of Career Motivation, Family Support, Cost, and Length of Education on Students’ Interest in Pursuing A Master's Degree in Accounting - Ni Putu Diah Indrawati; Ni Putu Sri Harta Mimba (International Journal of Economics, Management and Accounting, 2025)
Based on data from the Faculty of Economics and Business, Udayana University, interest in pursuing a master’s degree in accounting remains very low, while the demand for individuals with a strong educational background, good work ethic, and professionalism continues to increase. A master’s degree is a level of education that can be pursued after completing undergraduate studies (S1). This study aims to empirically examine the influence of career motivation, family support, cost, and duration of education on students’ interest in continuing their studies to the master's level in accounting. This research differs from previous studies in terms of location and the theoretical framework used. The population in this study consists of undergraduate accounting students from the 2021 cohort at universities in Bali that offer a master’s program in accounting. The sample was determined using probability sampling, specifically simple random sampling, resulting in 305 respondents. The data analysis technique used is multiple linear regression analysis. The results show that career motivation, family support, and duration of education have a positive and significant influence on students’ interest in pursuing a master’s degree in accounting, while education costs have a negative and significant influence.